Potential of the metaverse in enhancing learning experiences - Deden Riandi Putra; Ilhamuddin Marzuq; Salwa Tsabitah Navisa Eka Putri (Hipkin Journal of Educational Research, 2024)
Metaverse is nothing new, but it has only been widely discussed by people recently. Technology that continues to develop and is driven by influential people has made this technology attract the world's attention for its presence. It cannot be denied that in the current era, humans or not, like or not, live side by side with technology. Technology can be used by people of various ages and in various fields, including the field of education. The increasing demands in the world of education mean that the learning given to students must be more meaningful and reflect the daily life they go through to become functional human beings when they enter society. Metaverse is a new way to provide meaningful learning to students. Metaverse presents an authentic environment in a virtual world that allows students to continue interacting while learning more enjoyably. This can trigger students to be more enthusiastic about learning, and teachers can use various learning methods so the class does not get bored. This research uses a literature study method. This research aims to discover how Metaverse can play a role in the world of education.   Abstrak Teknologi yang terus berkembang mendorong penggunaannya pada bidang pendidikan untuk memberikan pengalaman pembelajaran yang lebih bermakna dan mencerminkan pada keseharian yang mereka lalui agar dapat menjadi manusia yang dapat berguna saat terjun ke lingkungan masyarakat. Metaverse dapat dijadikan sebagai solusi permasalahan tersebut dengan menghadirkan lingkungan yang sebenarnya pada dunia virtual dan memungkinkan kolaborasi peserta didik. Implementasi metaverse dalam pembelajaran tidak berjalan mulus, terdapat beberapa kendala yang dijumpai. Penelitian ini menyoroti konsep metaverse dalam pendidikan mencakup manfaat penggunaan, platform pembelajaran, tantangan, dan solusi penerapannya. Penelitian ini menggunakan metode studi literatur untuk mendapatkan hasil penelitian secara luas. Sumber yang digunakan berasal dari artikel jurnal ilmiah terbaru yang disaring dengan kriteria khusus. Temuan penelitian metaverse sebagai media pembelajaran yang menyenangkan dan memiliki berbagai platform dengan visual 3D memerlukan dukungan untuk pengembangan sumber daya. Dukungan dari pemerintah untuk menciptakan kurikulum dan kebijakan kemajuan teknologi pendidikan sangat diperlukan untuk mendukung penggunaan metaverse dalam media pembelajaran di Indonesia. Kata Kunci: Metaverse; pendidikan; teknologi